Nuansa dan Estetika Fenomena Budaya Tempatan: Perihal Ruang Sinematik dan Emosi dalam Gurindam Jiwa (1965): Nuances and Aesthetics of Local Cultural Phenomenon: Analysing Cinematic Space and Emotions in Gurindam Jiwa (1965) - Muhamad Farid Abdul Rahman; Mahyuddin Ahmad (Wacana Seni Journal of Arts Discourse, 2025)
This article attempts to extend the discourse on cinematic aesthetics by focusing on the under-studied dimension of purbawara films (also known as period costume dramas), by highlighting the aspect of shared cinematic identity. This can be perceived through the nuances and aesthetics of Asian melodrama, which emphasise the diverse emotions of characters and can be read as conveyed through cinematic space, fostering an interactive viewing experience between the spectator and the characters’ emotions via spatial aspects and cross-cutting techniques. Therefore, through the examination and discussion of the film Gurindam Jiwa (M. Amin 1965), this article argues that the shared cinematic identity of Asia is one of the elements that shape the unique nuances and aesthetics of purba films, observable through the complex assimilation of spatial, emotional, and intellectual aspects of the characters. Gurindam Jiwa tells the story of a romantic relationship between a husband and wife slowly evolving into a tragic tale due to suppressed emotions. This can be identified through the concept of “firasat” conveyed by the characters and translated through cinematic space (both interior and exterior) or in “babak bisu,” where viewers are only left with the emotions or facial expressions of the characters without dialogue, or scenes where characters do not speak but rather ponder their fate, accompanied by diegetic or non-diegetic sound. This intimate emotional space can be expressed by both men and women through their life experiences and perceptions. Therefore, by employing textual analysis methods and considering the aspects of cinematic space as well as local cultural phenomena such as “firasat,” “nestapa,” and the interplay among them, this article attempts to elaborate and weave together all these elements as a unique Asian value. This also contributes to a deeper understanding of the fluid and interconnected nature of Asian cinema through its shared cinematic cultural identity.